Inklusi Keuangan dan Penerimaan Pajak Daerah di Indonesia - Mifta Muzdalifah; Riatu Mariatul Qibthiyyah (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2023)
This study calculates the financial inclusion index, which includes three dimensions: 1) banking penetration, 2) availability of financial services, and 3) usage of financial services in 33 provinces in Indonesia from 2011-2019. The study aims to find empirical evidence on whether financial inclusion affects local tax revenue using the Fixed Effects Panel Data Model. The results show that Indonesia's average regional financial inclusion index is still in a low category. The financial inclusion index has a positive and significant effect on local tax revenue. The results are robust for taxes from different sources, such as provincial tax revenue, regencies/cities tax revenue, or local tax revenue.